CE-10 Cardiovascular events prior to or early after diagnosis of systemic lupus erythematosus in the systemic lupus international collaborating clinics cohort. (31st August 2016) - Urowitz, Murray; Gladman, Dafna; Anderson, Nicole; Su, Jiandong; Romero-Diaz, Juanita; Bae, Sang Choel; Fortin, Paul; Sanchez-Guerrero, Jorge; Clarke, Anne; Bernatsky, Sasha; Gordon, Caroline; Hanly, John; et al.
Abstract : Background: The objective of this study was to describe the frequency of myocardial infarction (MI) prior to the diagnosis of SLE and within the first 2 years of follow-up. Materials and methods: The SLICC atherosclerosis inception cohort enters patients within 15 months of SLE diagnosis. MIs were reported and attributed on a specialised vascular event form. MIs were confirmed by one or more of the following: abnormal EKG, typical or atypical symptoms with EKG abnormalities and elevated enzymes (≥2 times ULN), or abnormal stress test, echocardiogram, nuclear scan or angiogram. Descriptive statistics were used. Results: 31 of 1848 patients that entered the cohort had an MI. Of those, 23 patients had an MI prior to SLE diagnosis or within the first 2 years of disease. Of the 23 patients studied 60.9% were female, 78.3% were Caucasian, 8.7% Black, 8.7% Hispanic and 4.3% other. The mean age at SLE diagnosis was 52.5 ± 15.0 years. Of the 23 MIs that occurred, 16 MIs occurred at a mean of 6.1 ± 7.0 years prior to diagnosis and 7 occurred within the first 2 years of follow-up. Risk factors associated with early MI in univariate analysis are male sex, Caucasian, older age at diagnosis, hypertension, hypercholesterolemia, family history of MI and smoking. In multivariate analysis only age (OR = 1.06 95% CI: (1.03, 1.09)), hypertension (OR = 5.01, 95% CI: (1.38, 18.23)), hypercholesterolemia (OR = 4.43, 95% CI: (1.51, 12.99)) and smoking (OR = 7.50, 95% CI: (2.38, 23.57)) remained significant risk factors. Conclusions: In some lupus patients MI may develop even before the diagnosis of SLE or shortly thereafter, suggesting that there may be a link between autoimmune inflammation and atherosclerosis. Acknowledgements: This abstract is being submitted on behalf of the Systemic Lupus International Collaborating Clinics (SLICC) group.